Efficient network selection for computer-aided cataract diagnosis under noisy environment. (March 2021) - Pratap, Turimerla; Kokil, Priyanka
Highlights: An efficient network selection based robust computer-aided cataract diagnosis (CACD) method with AWGN is proposed. Feature extraction is done via CNN followed by locally- and globally-trained independent support vector networks (SVN). A suitable SVN is chosen using input retinal image noise level for accurate cataract diagnosis under AWGN conditions. The presented CACD scheme exhibits robust performance with AWGN than existing CNN based CACD methods, thus, it is superior. Abstract: Background and objective: Computer-aided cataract diagnosis (CACD) methods play a crucial role in early detection of cataract. The existing CACD methods are suffering from performance diminution due to the presence of noise in digital fundus retinal images. The lack of robustness in CACD methods against noise is a serious concern since even the presence of small noise levels may degrade the performance of cataract detection. However, noise in fundus retinal images is unavoidable due to various processes involved in the acquisition or transmission. Hence, a robust CACD method against noisy conditions is required to diagnose the cataract accurately. Methods: In this paper, an efficient network selection based robust CACD method under additive white Gaussian noise (AWGN) is proposed. The presented method consists a set of locally- and globally-trained independent support vector networks with features extracted at various noise levels. A suitable network is then selected based on the noise level present in the input image. The automatic feature extraction technique using pre-trained convolutional neural network (CNN) is adopted to extract features from input fundus retinal images. Results: A good-quality fundus retinal image dataset is obtained from EyePACS dataset with the use of natural image quality evaluator (NIQE) score. The synthetic noisy fundus retinal images are then generated artificially from good-quality fundus retinal images using AWGN model for effective analysis. The analysis is carried out with existing CNN based CACD methods at different noise levels. From results it is obvious that the proposed CACD method is superior in exhibiting robust performance against AWGN than existing CNN based CACD methods. Conclusions: From the experimental results, it is clear that the proposed method show superior performance against noise when compared with existing methods in literature. The proposed method can be useful as a starting point to continue further research on CNN based robust CACD methods.